Peran Internal Audit dalam Implementasi Enterprise Risk Management berupa Pelaporan Kerusakan Prosedur Risiko. - Indarti, Indarti (AKMENIKA, 2017)
Implementation of Enterprise Risk Management (ERM) by Internal Audit in an orga-nization or company becomes important because Internal Audit is expected to help the organization achieve its objectives by approaching systematic and discipline to evaluate and improve the effectiveness of risk management, control, and governance process. As for which affects it is the involvement of internal auditors, the relation-ship of the audit committee with the internal auditor, and ERM.This study aims to analyze the involvement of Internal Audit in Enterprise Risk mana-gement implementation. Internal auditors should assist both management and audit committees in risk management responsibilities and supervisory roles by examining, evaluating, reporting and recommending improvements to the adequacy and effec-tiveness of risk management processes. An interesting issue is whether internal auditors involved in corporate risk management have a link to the willingness of internal auditors to report to the audit committee.The population in this study are the internal auditors and audit committees who working in companies manufacturing and financial services. The reason for determining the company is because the researcher wants to know how internal audit is involved in ERM implementation on that entity. The sample used in this research is internal auditor at private company and at Banking in this case internal auditor at local bank.The analytical method used is multiple regression analysis with SPSS version 23 pro-gram. The analysis technique used in this research is descriptive statistical analysis, classical assumption test, F-statistic hypothesis test to test influence together with 5% confidence level and use t-statistics to test partial regression coefficients. This re-search was conducted to analyze how much influence the role of Internal Audit in applying Enterprise Risk Management in the implementation of Audit.The result of this research is that the high level of internal auditor involvement in Enterprise Risk management implementation has no significant and significant im-pact on reporting of damage to risk management procedures. This indicates that the role of internal auditors in corporate risk management does not affect the reporting of damage to corporate risk management procedures. While the characteristics of strong relationships between internal auditors and audit committees positively and significantly influence the reporting of risk procedures, this indicates that internal audits that have strong internal audit-audit committee relationships strongly support internal auditors who have high involvement to report damage Greater risk procedures.